An intramolecular inverse electron demand Diels–Alder approach to annulated α-carbolines - Ma, Zhiyuan; Ni, Feng; Woo, Grace H. C.; Lo, Sie-Mun; Roveto, Philip M.; Schaus, Scott E.; Snyder, John K. (Beilstein Journal of Organic Chemistry, 2012)
Intramolecular inverse electron demand cycloadditions of isatin-derived 1,2,4-triazines with acetylenic dienophiles tethered by amidations or transesterifications proceed in excellent yields to produce lactam- or lactone-fused α-carbolines. Beginning with various isatins and alkynyl dienophiles, a pilot-scale library of eighty-eight α-carbolines was prepared by using this robust methodology for biological evaluation.
Keywords: α-carboline; chemical diversity; inverse electron demand Diels–Alder; isatin; pyrido[2,3-b]indole; 1,2,4-triazine